Financial Performance and Company Zakah Payment on Islamic Banks in Indonesia - Fitri Yetty; Ade Nur Rohim; Praptiningsih Praptiningsih (LAA MAISYIR: Jurnal Ekonomi Islam, 2021)
Financial performance is an indicator of commercial functions in Islamic banks, along with zakah as an indicator of social function. The influence between the two is important to know in order to encourage efforts and strategies for developing Islamic banks. This article aims to describe the description of profitability and zakat payments of Islamic Commercial Banks and to verify the effect of profitability on company zakat payments. The research method used in this research is quantitative research methods using SPSS for data analysis. This study uses secondary data from five Islamic Commercial Banks as research samples from 14 existing BUS during the 2015-2019 period. This study found the fact that the variables ROA, ROE, and BOPO simultaneously have a significant effect on zakat. Meanwhile, ROA and ROE partially have a significant effect on zakat. While BOPO partially does not affect zakat.